1999
DOI: 10.2302/kjm.48.79
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Cognitive Rehabilitation for Memory Disorders.

Abstract: Progress in the neuropsychology of memory disorders has provided a foundation for development of cognitive rehabilitation for amnesic patients. Accumulating evidence in the past two decades suggested that certain training techniques could be beneficial to many amnesic patients, such as teaching and acquisition of domain-specific knowledge, motor coding, reality orientation, and meta cognition improvement. In this article we review and discuss the current trends in cognitive rehabil itation of memory disorders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…The third author corroborated the findings of the search conducted by the first author through replication of the search strategy, detailed review of abstracts screened, and review and discussion of included papers against search criteria. Cermak (1975), Goldstein and Malec (1989) and Kashima et al (1998) focused on the use of rote learning as a means of facilitating the learning and retrieval of specific information in patients with Korsakoff's Syndrome (KS). The findings from these 3 studies were variable, with Kashima et al (1998) and Goldstein and Malec's (1998) findings suggesting that the use of simple repetition is effective in training KS patients to remember specific information, whilst Cermak's (1975) findings indicated that rote learning was less effective than visual imagery and cued learning in facilitating KS patients' retrieval of verbal information.…”
Section: Figure 1 About Herementioning
confidence: 99%
See 2 more Smart Citations
“…The third author corroborated the findings of the search conducted by the first author through replication of the search strategy, detailed review of abstracts screened, and review and discussion of included papers against search criteria. Cermak (1975), Goldstein and Malec (1989) and Kashima et al (1998) focused on the use of rote learning as a means of facilitating the learning and retrieval of specific information in patients with Korsakoff's Syndrome (KS). The findings from these 3 studies were variable, with Kashima et al (1998) and Goldstein and Malec's (1998) findings suggesting that the use of simple repetition is effective in training KS patients to remember specific information, whilst Cermak's (1975) findings indicated that rote learning was less effective than visual imagery and cued learning in facilitating KS patients' retrieval of verbal information.…”
Section: Figure 1 About Herementioning
confidence: 99%
“…Cermak (1975), Goldstein and Malec (1989) and Kashima et al (1998) focused on the use of rote learning as a means of facilitating the learning and retrieval of specific information in patients with Korsakoff's Syndrome (KS). The findings from these 3 studies were variable, with Kashima et al (1998) and Goldstein and Malec's (1998) findings suggesting that the use of simple repetition is effective in training KS patients to remember specific information, whilst Cermak's (1975) findings indicated that rote learning was less effective than visual imagery and cued learning in facilitating KS patients' retrieval of verbal information. As there was no control group or comparison intervention in Kashima et al's (1998) study, their findings provide no evidence to indicate how effective simple repetition is in comparison to other strategies.…”
Section: Figure 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…Em seguida, visando à orientação espaço-temporal, era realizada a Terapia de Orientação para Realidade (TOR), na qual se trabalhavam os aspectos temporais (dia, mês e ano) e espaciais (local de realização do grupo, nome da instituição, cidade e Estado) com auxílio de pistas verbais e visuais por meio de um mural na parede (BOTTINO et al, 2002;KASHIMA et al, 1999).…”
Section: Dinâmica Do Grupo A) Aberturaunclassified
“…The literature indicates that patients with persistent cognitive problems may benefit from periodic neuropsychological reevaluations, which allow for the systematic analysis of the changes that occur in cognitive functioning, indicative of the benefits of treatment or the evolution of the neuropsychiatric state (Gruber & Yurgelun-Todd, 2001). In addition, neuropsychology provides techniques for cognitive rehabilitation that can help patients recognise their cognitive changes as consequences of alcohol abuse (Kashima, Kato, Yoshimasu, & Muramatsu, 1999;Wilson, 1999), improve cognitive function, and alleviate suffering and feelings of psychosocial inadequacy. It is known that rehabilitation accelerates improvement of the cognitive changes among people with alcohol dependence, greatly contributing to the acquisition of new abilities and to the success of treatment (Oudman, Van der Stigchel, Wester, Kessels, & Postma 2011;Roehrich & Goldman, 1993).…”
mentioning
confidence: 99%